Lean for systems engineering with lean enablers for systems engineering - Oppenheim, Bohdan W., 1948- (Hoboken, N.J. : Wiley, 2011)
'The book describes the cutting-edge field of Lean for Systems Engineering and the new intellectual product Lean Enablers for Systems Engineering, LEfSE, a comprehensive checklist of 194 practices of Systems Engineering, focused on creating value without waste in large technological programs.'--
Includes bibliographical references and index.
Keywords: Engineering economy; Systems engineering; Lean manufacturing